PEMBIAYAAN MURABAHAH BERMASALAH: Studi pada Bank Pembiayaan Rakyat Syariah di Kota Bandung - Suryanto, Suryanto; Dai, Ratna Meisa; Nursetyani, Evi (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2017)
This study aims to determine murabahah financing problem and how to handle it. The method used in this research using the descriptive method with the qualitative approach. Primary data sources were obtained using interviews and field observations. Secondary data were obtained through literature study related to murabahah problem and documentation study. The result of research indicates that murabahah financing in BPRS always related to wakalah contract. Wakalah is a contract between two parties in which one party submits, delegates, represents an affair to another party and the other undertakes the mandate at the request of the representative party. The cause of murabahah financing is problematic due to several factors, namely external and internal factors of the bank. External factors of the bank that comes from customers such as: losing in business competition, the business is run relatively new, side stream use of funds, the death of the key person, divorce key person, sick family members, and the character of customers who are not good. While the internal factors due to errors in conducting the analysis and weak aspects of supervision and monitoring. Handling of non-performing financing is done through collection activities, rescue activities (revitalization), settlement of guarantee activities and write off. Billing activities are done by contacting or visiting customers intensively, giving warning letters. Rescue of troubled financing is done by revitalizing rescheduling and restructuring. While write-off is a write-off of financing that is congested from on-balance sheets and recorded on the off-balance sheet. Keywords: murabahah, problem financing, sharia bank